The night before Christmas - Moore, Clement Clarke, 1779-1863 (Albert Whitman & Company, 2014)
"Barbara Reid reimagines everyone's favorite Christmas poem in her own extraordinary style, featuring a lively cast of young creatures anticipating the most exciting night of the year! The classic poem is brought to life by her signature Plasticine illustrations, full of humor and astonishing detail, making this a Christmas treasure to read year after year"--